EVALUASI PELAKSANAAN SENSUS PAJAK NASIONAL TERHADAP PENINGKATAN KESADARAN WAJIB PAJAK (STUDI KASUS PADA KPP PRATAMA SURABAYA MULYOREJO) - DWI LESTARI, WAHYU Dwi (Jurnal Akuntansi AKUNESA, 2014)
One of source of state revenue is from taxes. Tax is a source of revenue that used for the development implementation. This study aimed to analyze the effect of the presence of a Sensus Pajak Nasional (SPN) to increase awareness of the taxpayer. With the Sensus Pajak Nasional is expected to have a positive impact on increasing awareness of taxpayers.This study utilize one kualitatif’s approaching with one descriptive analysis that works through a topic by give delineation about that topic. The results of this study indicate that the implementation of the Sensus Pajak Nasional has influence in raising awareness of the taxpayer, the increase can be seen in the number of taxpayers who convey the SPT and NPWP after the holding of the Sensus Pajak Nasional.Keyword : Tax, Taxpayer, Sensus Pajak Nasional, Taxpayer’s awareness.